A comparative study for evaluating the performance of five coatings applied on Fe3O4 nanoparticles for inhibition of asphaltene precipitation from crude oil. Issue 11 (1st September 2020) - Setoodeh, Narjes; Darvishi, Parviz; Lashanizadegan, Asghar; Esmaeilzadeh, Feridun
Abstract: In this study, potential of Graphene oxide (GO), Silica (SiO2 ) and Chitosan coatings on Fe3 O4 magnetic nanoparticles was investigated for asphaltene adsorption. The comparison between coated and uncoated nanoparticles was made to evaluate the adsorption performance of coatings. The synthesis of nanoparticles was conducted using the co-precipitation method. All nanoparticles were verified using FT-IR, FESEM and XRD analyses. The experiments were performed in two stages. The different parameters effects such as temperature, initial concentration of nanoparticles and initial asphaltene concentration in the synthetic solutions were investigated in the first sets of experiments. Decrease of nanoparticles concentration and temperature and increase in initial asphaltene concentration resulted in increase of asphaltene adsorption capacities. GO-Fe3 O4 showed the highest adsorption efficiency followed by chitosan-Fe3 O4, Fe3 O4 and SiO2 -Fe3 O4 . The average values for adsorption efficiency were 70.47, 66.94, 64.56 and 65.94% for GO-Fe3 O4, chitosan-Fe3 O4, SiO2 -Fe3 O4 and Fe3 O4 nanoparticles, respectively. In the second stage, the tests with crude oil were performed using the optimum amount of nanoparticles concentration under atmospheric pressure and simulated reservoir conditions. The satisfactory results were obtained for improving adsorption of asphaltenes from crude oil similar to synthetic solution trends. The amount of adsorption increased with increasing pressure. The experimental data for adsorption isotherms models followed the Langmuir model. For adsorption kinetics, the pseudo-second-order Lagergren model showed more precise results. The results showed that we could apply appropriate coatings for inhibition of asphaltene precipitation and enhancement of asphaltene adsorption. However, the asphaltene adsorption amount depends strongly on the kind of coatings applied. Graphical Abstract: